Experiences of family caregivers of the older people with limitations in activities: A qualitative study. (4th November 2022) - S K Wijesiri, H S Maliga; Samarasinghe, K; Wasalathanthri, S; Wijeyaratne, CN
Abstract: Functional disabilities increase with ageing and limitations in daily living activities (ADLs) occurred as a consequence. Older people living at home may therefore become dependent on family members in managing activities in daily living. As the informal caregivers' role is known to be challenging, their experiences need to be explored to strengthen their new roles as family caregivers. This study aimed at exploring family caregivers' experiences of providing care for older people living at home with limited ADLs in Sri Lanka. Caregivers caring for older people with limitations in activities at home were purposively selected. Limitations in ADL were determined using the Sinhala‐validated Barthel Index. Data were collected through in‐depth interviews with 20 caregivers who cared for older people with several basic self‐care limitations. Data were analysed using thematic analysis. The results consist of three themes related to caring for older people with limited ADLs: committed to providing compassionate care for the activity‐limited older person, trapped in one's own home by caring for the activity‐limited older person and in need of respite and support in caring for older persons with limitations of activity. Motivated to care, adapting to care‐giving challenges, changed life pattern, neglecting one's own health, emotional suffering, lack of knowledge and skills and wanting assistance in care‐giving and with financial support were resultant subthemes. Family caregivers of older people with limited activities living at home, face many challenges to their own health. Supporting interventions will therefore be necessary. An introduction of educational training programmes for informal caregivers would promote the health and well‐being of functionally disabled older people and their caregivers. Developing home‐based care will be a future solution since the availability of informal caregivers will be at risk due to a rapid increase in older people and social changes related to the family structure.